The Effect of Promotions and Online Customer Reviews on Purchase Decisions Mediated by Brand Image on Erigo Products on Shopee E-Commerce - Novelayanti, Melati Desi; Wulandari, Anna; Yahya, Adibah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the effect of promotions and online customer reviews on purchase decisions mediated by the brand image of Erigo products in Shopee e-commerce. Data were collected through questionnaires distributed to Erigo consumers who shop through Shopee. The data analysis method used is Partial Least Squares (PLS) with the help of SmartPLS application. This study concludes that promotions and online customer reviews directly influence purchase decisions; however, brand image is not a significant mediator in this relationship. These findings imply that effective promotion strategies and online customer review management can enhance purchase decisions, even though the brand image does not directly mediate this relationship for Erigo products on Shopee.